Possible participation of IgG4 in the activation of complement in IgG4-related disease with hypocomplementemia. Issue 2 (3rd March 2016) - Sugimoto, Mitsuru; Watanabe, Hiroshi; Asano, Tomoyuki; Sato, Shuzo; Takagi, Tadayuki; Kobayashi, Hiroko; Ohira, Hiromasa
Abstract: Objective : To investigate which IgG subclasses contribute to the activation of the complement pathway in IgG4-related disease (IgG4RD) patients with hypocomplementemia. Methods : Sera of IgG4RD patients were analyzed for the binding ability of IgG subclasses to complement component 1q (C1q). Polyethylene glycol (PEG) precipitates containing immune complexes (ICs) in sera of IgG4RD patients were analyzed for IgG subclass composition by Western blotting. PEG precipitates containing ICs (PEG-ICs) in sera of patients were also analyzed for their ability to consume complement in normal human serum (NHS) using a total complement hemolytic (CH50) assay and a commercial kit to measure the complement capacity of all three individual complement pathways. Results : The C1q binding assay revealed high serum levels of C1q-binding IgG4 in IgG4RD patients with hypocomplementemia. ICs in PEG precipitates were formed with IgG4 in IgG4RD patients, regardless of the presence or absence of hypocomplementemia. We observed a marked reduction of CH50 and reduced complement activity in the classical complement pathway as well as the mannan-binding lectin complement pathway in NHS incubated with PEG-IC isolated from IgG4RD patients with hypocomplementemia. Conclusion : Our results suggest that IgG4 may participate in the activation of complement in IgG4RD patients with hypocomplementemia.